The association between serum sodium level and tuberculous meningitis compared with viral and bacterial meningitis - Seunghee Na (Nature Portfolio, 2021)
Abstract We evaluated the association between hyponatremia and tuberculous meningitis (TBM) with the aim of providing additional information for differential diagnosis from other types of infectious meningitis, especially viral meningitis (VM). Cross-sectional and longitudinal data involving 5026 participants older than 18 years were analyzed in the total population and a propensity-matched population. The initial and lowest sodium levels and longitudinal changes in TBM, bacterial meningitis (BM), and VM patients were compared. Participants in the TBM group were enrolled when they were diagnosed as possible, probable, or definite TBM according to the Marais’ criteria. The initial serum sodium level was significantly lower in TBM patients than in BM and VM patients (136.9 ± 5.9 vs. 138.3 ± 4.7 mmol/L, p < 0.001 for TBM vs. BM, and 139.0 ± 3.1, p < 0.001 for TBM vs. VM), and it decreased significantly more steeply to lower levels in both the TBM and BM patients compared with VM patients. The lowest serum sodium level was in the order of TBM < BM < VM patients, and the change was statistically significant in all subgroups (131.8 ± 6.4, 133.1 ± 5.1, 137.4 ± 3.7, respectively, p < 0.001). Participants with lower serum sodium level were more likely to have a diagnosis of TBM rather than VM, and this association was more pronounced for the lowest sodium level than the initial sodium level [OR 4.6 (95% CI 2.4–8.8, p < 0.001)]. These findings indicate that baseline and longitudinal evaluation of serum sodium level can provide information for differential diagnosis of TBM from BM or VM.